2021
DOI: 10.1002/adom.202100291
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Formation of Hybrid Nanocrystal Gels: Deposition of Metal Domains on CdSe/CdS Nanorod and Nanoplatelet Networks

Abstract: Hybrid semiconductor‐based nanocrystals (NCs) are generally synthesized in organic media prior to their assembly into catalytically promising nanostructures via multistep methods. Here, a tunable, easy‐to‐adapt and versatile approach for the preparation of hybrid nanoparticle networks from aqueous nanocrystal solutions is demonstrated. The networks consist of interconnected semiconductor NC backbones (made of CdSe/CdS dot‐in‐rods or core/crown nanoplatelets) decorated with noble metal (Au and Pt) or with metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…[ 28 ] Zámbó et al observed an in situ gelation and noble metal domain formation upon addition of multivalent metal ions to similar semiconductor nanocrystal building blocks resulting in a continuous semiconductor network with more homogeneous domain distribution. [ 11,29 ] Moreover, the use of hybrid nanostructures and alloys in photoelectrochemical applications has been shown for TiO 2 /Pt, [ 30 ] Zn 1− x Cd x Se/Pt, [ 31 ] and CdSe/CdS/Pt systems. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ] Zámbó et al observed an in situ gelation and noble metal domain formation upon addition of multivalent metal ions to similar semiconductor nanocrystal building blocks resulting in a continuous semiconductor network with more homogeneous domain distribution. [ 11,29 ] Moreover, the use of hybrid nanostructures and alloys in photoelectrochemical applications has been shown for TiO 2 /Pt, [ 30 ] Zn 1− x Cd x Se/Pt, [ 31 ] and CdSe/CdS/Pt systems. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%
“…Due to the position of the Fermi level of noble metals, electrons typically accumulate in the metal domain, opening new non-radiative recombination pathways that manifest themselves in photoluminescence quenching. [23] In solution ensembles, photoluminescence (PL) quenching was demonstrated for hybrid nanocrystals consisting of Au-decorated CdSe nanorods [24] with different Au domain sizes. Hybrid nanomaterials consisting of co-gelated semiconductor and noble metal nanocrystal (Ag or Au) network further extended the potential applications of such structures in optoelectronic devices as well as in photocatalytic reactions via utilizing the separated electrons and holes in, for example, redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the position of the Fermi level of noble metals, electrons typically accumulate in the metal domain, opening new non‐radiative recombination pathways that manifest themselves in photoluminescence quenching. [ 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…In general, self‐assembly of nanoparticles can link the favorable microscopic characteristics to the macroscopic application and might even generate new properties. [ 21–29 ] So far, NPLs could not only be assembled randomly for example as (cryo‐)aerogels [ 26,28,30,31 ] but also possess a high tendency to form ordered stacks. [ 24,32–36 ] Due to their highly anisotropic shape, the self‐assembly is favored along the axial direction (in the direction of the thickness).…”
Section: Introductionmentioning
confidence: 99%